EFFECT OF VITAMIN C, E AND SELENIUM ON HAEMATOLOGICAL AND SERUM BIOCHEMISTRY OF ADULT MALE GUINEA PIGS (FUDMA JOURNAL OF SCIENCES, 2024)
The study was conducted to assess the biopotency of antioxidant supplements on physiological, testicular, and oxidative biomarkers in adult male guinea pigs (Cavia porcellus). A total of 60 adult male guinea pigs of three months of age with an average body weight of 500±20g were randomly allocated into three dietary treatment groups of vitamin C, E and Selenium and each comprised four varying levels with five animals per group in a completely randomized design (CRD). Feed and water was provided ad-libitum. Haematological concentration of guinea pigs in this study indicated a significant (P0.05) difference on Plasma Albumin, Globulin, Total protein, Alanine aminotranferase and Alkaline phosphate of animal supplemented with varying dosage of vitamin E and Selenium. However, a significant (P
Keywords: Guinea pigs; Haematology; Serum; Vitamins; Selenium